Effects of local food attributes on tourist dining satisfaction and future: The moderating role of food culture difference. Issue 1 (2nd January 2022) - Kim, Seongseop (Sam); Choe, Ja Young (Jacey); Kim, Peter Beomcheol
ABSTRACT: This study aims to investigate the effects of local food attributes on tourists' dining satisfaction and future intention in Hong Kong. In addition, the moderating effect of food culture difference on the relationship between local food attributes and tourists' dining satisfaction was examined. Surveys from 1, 274 tourists who had tasted local food in Hong Kong were used for data analyses. The moderating effect of food culture on the relationship between food novelty and satisfaction was larger for tourists whose home food culture was similar to the Hong Kong's food culture. By contrast, the moderating effect of food culture on the relationship between food quality and satisfaction was larger for tourists from a food culture that was different from the Hong Kong's food culture. Hong Kong destination marketers could include distinctive and unusual features of local food in their promotional material with the knowledge that food culture difference affects tourists' dining satisfaction. The integration of local food into food culture difference using multilevel analysis offers constructive theoretical and practical implications.